The expression you have given is not an equation (does not equal something), so it cannot be solved. I am going to assume that the expression is supposed to equal zero, and then solve that equation.
The equationthat I am going to solve is 2x2 - 9x + 4 = 0. The method I am going to use is called completing the square.
2x2 - 9x + 4 = 0
2x2 - 9x + 4 -4 = 0 -4 Subtract 4 from each side
2x2 - 9x = -4 Simplify
(2x2 - 9x)/x = -4/2 Divide both sides by two (the coefficient of x2)
x2 -9/2*x = -2 Distribute on the left, simplify the right
x2 - 9/2*x + 81/16 = -2 + 81/16 Add 81/16 to each side (divide the coefficient on x by two, then square
(x - 9/4)2 = -2 + 81/16 Factor the left side as a perfect square (9/4 is the square root of
(x - 9/4)2 = -32/16 + 81/16 Change the fractions on the right so that they have common
(x - 9/4)2 = 49/16 Simplify
x - 9/4 = +/- sqrt(49/16) Take the square root of both sides (sqrt means square root)
x - 9/4 = +/- 7/4 Simplify
x - 9/4 = 7/4 or x -9/4 = -7/4 Separate the problem into positive and negative values on the right
x - 9/4 + 9/4 = 7/4 +9/4 or Add 9/4 to both sides on both possible solutions
x - 9/4 + 9/4 = -7/4 + 9/4
x = 16/4 or x = 2/4 Simplify each solution
x = 4 or x = 1/2 Reduce the fractions
Completing the square is a valuable tool to use, because any binomial equation can be solved with it. Even though you could find the answer to this problem without it, I wanted to give you a chance to learn how to use it.